2021
DOI: 10.3389/fnagi.2021.619916
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Level of 24S-Hydroxycholesterol and Polymorphism of CYP46A1 SNP (rs754203) Are Associated With Mild Cognitive Impairment in Patients With Type 2 Diabetes

Abstract: BackgroundAbnormal cholesterol metabolism is common in type 2 diabetes mellitus (T2DM) and causes dementia. Cholesterol 24S-hydroxylase (CYP46A1) converts cholesterol into 24S-hydroxycholesterol (24-OHC) and maintains cholesterol homeostasis in the brain.ObjectiveThis study aimed to investigate the roles of 24-OHC and the CYP46A1 (rs754203) polymorphism in patients with T2DM and mild cognitive impairment (MCI).MethodsA total of 193 Chinese patients with T2DM were recruited into two groups according to the Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…For example, age-related macular degeneration (AMD) results in elevated levels of circulatory 24HC [28][29][30]34 . Moreover, several neurological and metabolic conditions (e.g., Alzheimer's, glaucoma, obesity) affect plasma 24HC concentration [23][24][25][26][28][29][30]34 . Thus, 24HC levels in circulation during various pathophysiological conditions may regulate cellular immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, age-related macular degeneration (AMD) results in elevated levels of circulatory 24HC [28][29][30]34 . Moreover, several neurological and metabolic conditions (e.g., Alzheimer's, glaucoma, obesity) affect plasma 24HC concentration [23][24][25][26][28][29][30]34 . Thus, 24HC levels in circulation during various pathophysiological conditions may regulate cellular immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…24HC is also called cerebrosterol since it plays an important role in maintaining cholesterol homeostasis in the brain 22 . It has also been implicated in several diseases, including Alzheimer's, glaucoma, and obesity [22][23][24][25][26] . The conversion of the blood-brain barrier impermeable cholesterol to highly permeable 24HC and transport to the peripheral/ systemic circulation is regarded as a major mechanism of cholesterol removal from the brain to maintain cholesterol homeostasis [26][27][28][29][30] .…”
mentioning
confidence: 99%
“…Pathways include hemostasis [57], neutrophil degranulation [58], immune system [59] and cytokine signaling in immune system [60] are responsible for progression of GDM. LGR5 [61], GREM1 [62], GLRA3 [63], NEUROD4 [64], CYP2J2 [65], KCNH6 [66], LBP (lipopolysaccharide binding protein) [67], CXCL14 [68], RGN (regucalcin) [69], NPY2R [70], SERPINB13 [71], WNT5A [72], EDA (ectodysplasin A) [73], HSD11B2 [74], ACVR1C [75], NEUROD1 [76], SLIT2 [77], PPARGC1A [78], IGF1 [79], OSR1 [80], CYP46A1 [81], TLR3 [82], BMP7 [83], SELP (selectin P) [84], HLA-A [85], NOTCH2 [86], LRP1 [87], CLU (clusterin) [88], FCN1 [89], CDKN1A [90], SMAD3 [91], HLA-E [92], PTPRC (protein tyrosine phosphatase receptor type C) [93], MYH9 [94], JAK3 [95], IL6R [96], TIMP1 [97], DOCK8 [98], TNFRSF1B [99], ITGAL (integrin subunit alpha L) [100], CD47 [101], RARA (retinoic acid receptor alpha) [102], DGKD (diacylglycerol kinase delta) [103], PLEK (pleckstrin) [104], PREX1 [105], BSCL2 [106], PANX1 [107], IRF7 [108], NOTCH1 [109], STIM1 [110], TRIM13 [111], LRBA (LPS responsive beige-like anchor protein) [112], CXCR4 [113], MDM4 [114], MYO9B [115] and PDE5A [116] were revealed to be expressed in diabetes mellitus, but these genes might be novel targets for GDM. SIX1 [117], GREM1 [118], GHRHR (growth hormone releasing hormone receptor) [119], GPR37L1 [120], CYP2J2 [121], AQP4 [122], ROS1 [123], LBP (lipopolysaccharide binding protein) [124], SGCD (sarcoglycan delta) [125], CXCL14 [126], RGN...…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Recent study in China has shown that high level of plasma 24S‐hydroxycholesterol (24S‐OHC) and C‐carrier genotype of CYP46A1, 24‐hydroxylase (CYP26A1) polymorphism rs754203 was related to high risk reduction in attention and executive function, was converted from cholesterol mediated by CYP46A1. [ 20 ] 24S‐OHC is the pathway of cholesterol elimination from the brain in addition to 27‐OHC, the balance of 27‐OHC and 24S‐OHC is essential for AD development. [ 21 ] Various studies have reported the polymorphism of cholesterol related gene was essential for AD, however, no research concerned about CYP27A1 polymorphism and the interaction effect with 27‐OHC.…”
Section: Introductionmentioning
confidence: 99%